Pengaruh Model Pembelajaran Kooperatif Tipe Picture and Picture Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Pencemaran Lingkungan - Rabiatul Qamariyah; Andri Wahyu Wijayadi (CAHAYA: Journal of Research on Science Education, 2026)
The quality of learning is strongly influenced by the learning model used by the teacher. Observations revealed that seventh-grade students' understanding of environmental pollution material remained low due to the dominance of conventional teaching methods. Therefore, an innovative learning model is needed to enhance students' motivation and activeness. One promising alternative is the cooperative learning model of the Picture and Picture type. This study aims to examine the effect of the cooperative learning model of the Picture and Picture type in improving the learning outcomes of seventh-grade students at MTs on the topic of environmental pollution. A quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design, was employed. The experimental group was taught using the Picture and Picture model, while the control group was taught using conventional methods. Data were collected through pretests and posttests and analyzed using the Wilcoxon Signed Ranks Test due to non-normally distributed data. The results showed that the average score of the experimental group increased from 62.10 to 91.57 (a gain of 31.05 points), which was higher than that of the control group, which only increased by 21.57 points. The Wilcoxon test yielded a significance value of 0.001 (p < 0.05), indicating a significant difference between the pretest and posttest scores. Thus, the Picture and Picture cooperative learning model is proven to be more effective than conventional methods in improving students' learning outcomes on environmental pollution material